Hybrid E-Training Measurement Tool: Reliability and Validity - Din, Rosseni; Nordin, Norazah; Jusoff, Kamaruzaman; Nordin, Mohamad Sahari; Zakaria, Shanudin; Mastor, Khairul Anwar; Embi, Mohamad Amin (IDOSI Publications, 2011)
Hybrid E-Training had become prevalent in the field of computer and educational technology for both who were in the field and not exactly in the field. This paper discussed the e-Training being conducted in a hybrid environment. The objective of this paper was to examine the validity and reliability of the items on assessing perception towards the Hybrid E-Training system. The instrument used for the research was a set of questionnaire to measure the meaningfulness of the Hybrid e-Training. The number of samples is 213. The result showed that the overall reliability coefficient for the items on assessing perception towards the Hybrid E-Training system was 0.986. Reliability at the scale levels for these items was also acceptable, ranging from 0.886 to 0.971. Overall analyses suggested that these items were reliable to measure a hybrid e-Training system. It would be interesting to further investigate as to whether or not learning style is a mediating or a moderating factor towards achieving meaningful learning via the use of hybrid e-training programs as modelled in the final results.